Thermal fluid mathematical modelling of twin roll casting (TRC) process for AZ31 magnesium alloy. (1st August 2013) - Hadadzadeh, A; Wells, M A
Abstract : A two-dimensional computational fluid dynamics (CFD) thermal fluid model has been developed and validated for twin roll casting (TRC) of AZ31 magnesium alloy using the commercial package ANSYS CFX. The model was developed to represent the steady state part of the TRC process. The thermal history of the strip was studied in terms of the temperature gradient through the strip thickness at the exit of the caster, the sump depth and mushy zone thickness at the centreline for different casting speeds, final strip thicknesses and heat transfer coefficients between the rolls and the surface of the strip. Moreover, the effect of these parameters on the average solidification cooling rate and secondary dendrite arm spacing in the solidified structure was investigated. Model validation was done by comparing the predicted and measured exit strip surface temperature as well as the secondary dendrite arm spacing (SDAS) through the thickness of the sheet to those measured using the Natural Resources Canada Government Materials Laboratory, CanmetMATERIALS located in Hamilton, Ontario, Canada. Analysis of the effect of TRC conditions on the SDAS showed that more uniform SDAS through the thickness is obtained when casting thinner strips at higher casting speeds.